2009
DOI: 10.1021/la901646d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surfactants in the Interaction of Dye Molecules in Natural DNA Polymers

Abstract: Solutions and powders formed from salmon sperm deoxyribonucleic acid (DNA) reacted with the cationic surfactant cetyltrimethylammonium chloride (CTMA-Cl) incorporated fluorescent rhodamine molecules: anionic sulforhodamine 640 (SRh) or cationic/zwitterionic rhodamine 640 perchlorate (RhP). The role of the cationic surfactant in the interaction between rhodamine dye and DNA-surfactant molecules has been investigated in both solution and solid state using optical spectroscopy and electrophoresis. Unexpectedly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…11,13 In our case we immersed DNA-CTMA complex films into acetone solution of DMASPDB, because the complex was insoluble to acetone as well as water or DMF. Fig.…”
Section: Hemicyanine Devices Prepared By Immersion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,13 In our case we immersed DNA-CTMA complex films into acetone solution of DMASPDB, because the complex was insoluble to acetone as well as water or DMF. Fig.…”
Section: Hemicyanine Devices Prepared By Immersion Methodsmentioning
confidence: 99%
“…11 There are many water soluble xanthene dyes available as eosin and fluorescein as well as rhodamines, the most popular laser dyes. Eosin Y is an anionic dye and is important for staining of biological materials for microscopic observation, but it has not been studied as a laser medium.…”
Section: Eosin Y Devices Frepared With Water Solusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological material based on deoxyribonucleic acid-cetyltrimethylammonium complex (DNA-CTMA) has been considered as the potential candidate material for the bioelectronics and biophotonics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. CTMA is a kind of surfactant and often used to modify DNA sodium salt, which interacted with DNA helix statically.…”
Section: Introductionmentioning
confidence: 99%
“…While the binding of cationic porphyrins and Cu (II) phthalocyanine (Cuprolinic blue) with DNA itself has been well-investigated and the binding patterns characterized [2][3][4], little or no study has been reported with regard to their binding to DNA cationic complexes such as DNA-CTMA. While there are literature reports involving some active layers incorporating DNA-CTMA and fluorescent organic dyes such as sulforhodamine with some emphasis on their binding characteristics [5,6], the methodology described in this paper will be of general utility in the study of binding between DNA-CTMA and various organic additives of electronic/optical interest for device applications.…”
Section: Introductionmentioning
confidence: 99%